Identifying The Variables Of Entrepreneurship Education, Digital Literacy, And Motivation On Entrepreneurship Interest - Bayu, Purwanto bayu nugroho (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract This study is intended to determine the effect of entrepreneurship education, digital literacy, and motivation on students' interest in entrepreneurship. In addition, to determine several indicators of variables of entrepreneurship education, digital literacy, and motivation and students' interest in entrepreneurship that can be used as references by further researchers. Several factors that contribute to interest in entrepreneurship include entrepreneurship education, digital literacy and motivation. Based on previous studies, entrepreneurship education, digital literacy, motivation have a significant influence on interest in entrepreneurship. Keywords:Entrepreneurship Education, Digital Literacy, Entrepreneurial Motivation, Interest in Entrepreneurship